Choroidal detachment in perforated corneal ulcers: frequency and management. Issue 9 (24th May 2006) - Singh, R; Umapathy, T; Abedin, A; Eatamadi, H; Maharajan, S; Dua, H S
Abstract : Aims: To determine the frequency of choroidal detachment (CD) in eyes with non-traumatic corneal ulcer perforation and, also, to assess the efficacy and safety of cyanoacrylate glue in sealing corneal perforations. Methods: 18 eyes of 17 patients were studied. Inclusion criterion was any patient with a non-traumatic perforated corneal ulcer. All patients had a thorough history taken and complete ophthalmic examination including B-scan ultrasonography. Patient demographics, presence of CD, and efficacy of corneal gluing were assessed. Results: Eight of the 18 eyes (44%) were documented to have a CD. Among perforations of >2 mm 2, six eyes (75%) were documented to have CD compared with two eyes (20%) with perforations of ⩽2 mm 2 (p = 0.054). No correlation could be determined between perforation duration and incidence of CD. Of the 15 eyes that underwent gluing, there were 13 successes (87%) and two failures (13%). Within the successes four patients (27%) required re-gluing because of infection (one patient) or progression of melt and glue loosening (three patients). Failure was the result of severe progression of melting (one patient) and a very large perforation (one patient). Conclusion: Choroidal detachment following corneal ulcer perforation is common and is more likely in larger corneal perforations. Preoperative B-scan should be considered in cases of large corneal perforations requiring therapeutic keratoplasty to document choroidal detachment, which if large may require drainage. Cyanoacrylate glue is an effective and safe method for sealing small corneal perforations. A vigil must be maintained for infection while the glue and bandage contact lens are in situ.